Phosphorus availability and speciation in soils amended with upcycled dairy-waste nutrients - Laan, Maggi; Strawn, Daniel G.; Kayler, Zachary E.; Cade-Menun, Barbara J.; Möller, Gregory (Frontiers in Chemical Engineering, 2024)
The excessive application of dairy manure to soils to supply plant nutrients can result in increased offsite nutrient transport and degraded water quality. However, by concentrating nutrients from dairy-waste onto biochar or as biosolids, a viable alternative fertilizer can be produced that will benefit soil health, promote carbon sequestration, and decrease nutrient leaching into surface waters. In this study, a greenhouse experiment was conducted to assess soil phosphorus (P) speciation and barley plant growth in soils amended with dairy-waste treated biochar and fermented manure. Phosphorus characterization in the post-harvest soils was determined using selective extractions, 31 P-NMR and XANES spectroscopy, and isotopic tracing (P-δ 18 O). Selective extractions and NMR spectroscopy revealed that most of the P in the amended soils occurred as inorganic species (>85%). XANES spectroscopy further showed that the soil P occurred as either calcium-P minerals (54% -87%) or adsorbed P (0% -46%) species. Analysis by P-δ 18 O in water and sodium bicarbonate extractions of the treated soils showed that the water-extracted P pool is cycled much faster than the sodium bicarbonate extracted P. Although less than 10% of the total P in the dairy-derived bioproducts was extracted using water, plant productivity in the soils treated with these amendments was the same as that in soils treated with equivalent amounts of conventional nitrogen and P fertilizer. This suggests that dairy-derived bioproducts are good soil amendments to supply nutrients and limit leaching.